Strategi pengembangan pariwisata daerah dan pemberdayaan masyarakat di Parigi Moutong - Soedarso Soedarso; Sutikno Sutikno; Sukardi Sukardi (Masyarakat, Kebudayaan dan Politik, 2016)
Community empowerment program in Parigi Moutong district has not been effectively operated, that greater effort to evaluate and develop the previously implemented program is needed. This research uses purposive sampling method, i.e. the chosen sample method. The study result finds that the cause of the community empowerment program that has been done is still not effective because the process of the determining program is lacking of public participation. As a result, it creates a new helplessness, i.e. the dependence of communities on the program with direct assistance. On the other hand, the regional tourism development program has a good prospect and able to synergized with a more participative community empowerment program that. The beauty of Parigi Moutong natural landscape and its possesion of various natural resources is a great potential to create a tourism destination, and enhancing society's welfare around the area.